2014
DOI: 10.1074/jbc.m114.547604
|View full text |Cite
|
Sign up to set email alerts
|

Lipin 2 Binds Phosphatidic Acid by the Electrostatic Hydrogen Bond Switch Mechanism Independent of Phosphorylation

Abstract: Background: Lipin 2 is a phosphatidic acid phosphatase (PAP) responsible for DAG formation at the ER membrane during lipogenesis. Results: A combination of biochemical approaches is used to characterize lipin 2 phosphatase activity and regulation. Conclusion: The electrostatic charge of PA regulates activity, but phosphorylation does not.Significance: These findings demonstrate differential regulation of PAP activity within the lipin family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 41 publications
2
54
0
Order By: Relevance
“…However, a sampling of k cat /K m values from this analysis ( (20,(22)(23)(24), similar to those of C1 and C2 enzymes (21,22,(25)(26)(27). Overall, the finding that C0 members, which have the most minimal cap inserts, are equally efficient and more specific than the other subfamilies suggests that incorporation of additional domains leads to the expansion of the substrate repertoire in the HADSF.…”
Section: Resultsmentioning
confidence: 93%
“…However, a sampling of k cat /K m values from this analysis ( (20,(22)(23)(24), similar to those of C1 and C2 enzymes (21,22,(25)(26)(27). Overall, the finding that C0 members, which have the most minimal cap inserts, are equally efficient and more specific than the other subfamilies suggests that incorporation of additional domains leads to the expansion of the substrate repertoire in the HADSF.…”
Section: Resultsmentioning
confidence: 93%
“…Although the intrinsic catalytic activity of lipin 2 is lower than lipin 1 ( 4 ), lipin 2 is subject to less regulation by phosphorylation ( 50 ). Lipin 2 protein abundance was increased in Alb-Lpin1 Ϫ / Ϫ liver.…”
Section: Discussionmentioning
confidence: 92%
“…A wealth of data now supports our understanding of lipin phosphorylation and its ability to regulate localization and activity (5,66,87,(94)(95)(96)(97). Other lipin kinases remain to be identified and the direct effect of phosphorylation on enzymatic activity needs to be further elucidated (95).…”
Section: Lipins -Biochemical Regulation I Insulin and Phosphorylationmentioning
confidence: 90%
“…More specifically, inhibition of mTOR and reduction in the phosphorylation of lipin 1, allow its translocation to the ER membrane and nucleus (66,85,93,96,97). We have shown that while lipin 1 is regulated by phosphorylation in vitro, the activity and localization of lipin 2 are not (94).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation